2022
DOI: 10.30773/pi.2021.0247
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Psychiatric Visits and Psychiatric Medication Prescription Among People Tested for SARS-CoV-2 During the Initial Phase of COVID-19 Pandemic in South Korea

Abstract: Objective The objective of this study was to monitor the trend of psychiatric visits and medication prescriptions among people tested for SARS-CoV-2 during the initial phase of coronavirus disease 2019 (COVID-19) pandemic in South Korea.Methods We conducted a population-based cohort study using data from the National Health Insurance Service (NHIS) linked to the Korea Disease Control and Prevention Agency (KDCA) data. The overall trend of psychiatric visits during COVID-19 for each month was compared to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In addition, schools are also a means of spreading SARS-COV in Korea, with a high risk of causing community transmission at schools (Choe et al, 2022). Interestingly, with several victims due to Sars -Cov in South Korea, it turns out that the form of medicine and patient visits that are mostly due to Sars-Cov are regarding mental health and psychiatry as a form of pandemic and the initial epidemic of Sars-Cov (Kim et al, 2022).…”
Section: Community Awareness and Disciplinementioning
confidence: 99%
“…In addition, schools are also a means of spreading SARS-COV in Korea, with a high risk of causing community transmission at schools (Choe et al, 2022). Interestingly, with several victims due to Sars -Cov in South Korea, it turns out that the form of medicine and patient visits that are mostly due to Sars-Cov are regarding mental health and psychiatry as a form of pandemic and the initial epidemic of Sars-Cov (Kim et al, 2022).…”
Section: Community Awareness and Disciplinementioning
confidence: 99%
“…As shown in Figure 1, group privacy issues can cause more consequences compared to individual privacy issues. Amid the intrusion into one's personal life in the above two real-world examples, some members committed suicide due to aggressive technologies' usage of big data and AI technologies with the fine-grained personal data of targeted groups [8][9][10]. Due to technical advancements in most fields, privacy threats to group privacy are increasing in recent times, and quick remedies are needed towards this genuine problem of big data technologies.…”
Section: The Emergence Of Group Privacy Issues: a New Dimensionmentioning
confidence: 99%
“…This impact seemed to be stronger in individuals infected by the disease than in those not infected [ 4 , 5 ]. More specifically, several studies have indicated that COVID-19 patients have more symptoms of anxiety, post-traumatic stress, depression, insomnia and suicidal thoughts [ 4 , 6 11 ]. One hypothesis for this is that direct viral infection of the central nervous system or through immune response may cause psychiatric disorders [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%